Investigación-acción participativa en el barrio de San Cristóbal de los Ángeles (distrito de Villaverde, Madrid) - Alguacil Gómez, Julio; Basagoiti Todríguez, Manuel; Camacho Gutiérrez, Javier (Cuadernos de Trabajo Social, 2006)
This study is the result of institutional collaboration between the Municipal Housing Office of the Ayuntamiento de Madrid (the body which is responsible for the Integral Rehabilitation Plan of the San Cristobal de los Angeles Quarter and the financing of the study) and the Universidad Carlos III de Madrid (which is responsible for its technical execution). Also, this project would not have been possible without the participation of a great number of people, residents of the neighbourhood, social organizations and public institutions committed to the quarter and its people. The motivating idea for all involved has been, on the one hand, the conviction that all urban improvements must be accompanied by a social intervention process in other aspects of Community Development (education, employment, culture, participation, social cohesion, etc.) and, on the other hand, the complete confidence in the potential that San Cristobal has as a space for coexistence and for relationships based on the values of respect, solidarity and democracy.